Ajde na oro! – The Day of Culture of the Republic of North Macedonia in Hungary as a science communication model - Bólya, Anna Mária (Macedón Tudományos és Kulturális Közlemények, 2025)
On 24 November 2024, the Ohrid Macedonian Folk Ensemble, in cooperation with several institutions, organized the first Day of the Culture of the Republic of North Macedonia in Hungary. Although settlers from the territory of today’s Republic of North Macedonia arrived in several waves from the sixteenth century onward, this diverse culture, rich in values and unique features, has received relatively little attention in Hungarian science communication. Events that place the dance house within an academic framework and interpret it as an activity of knowledge dissemination are particularly rare. The study examines the event, created through the collaboration of several artistic and academic institutions, as a case study and presents how a community-based cultural programme built around the dance house tradition can function as an effective model for scientific outreach.